P003 Randomised, placebo-controlled study of solriamfetol for excessive daytime sleepiness in narcolepsy types 1/2. (19th November 2019) - Black, Jed; Dauvilliers, Yves; Plazzi, Giuseppe; Shapiro, Colin M; Mayer, Geert; Corser, Bruce C; Emsellem, Helene A; Chen, Dan; Carter, Lawrence P; Wang, Hao; Thorpy, Michael J
Abstract : Introduction: Solriamfetol (formerly JZP-110), a dopamine and norepinephrine reuptake inhibitor, has been approved in the United States to improve wakefulness in adults with excessive daytime sleepiness (EDS) associated with narcolepsy (75–150 mg) or obstructive sleep apnoea (OSA; 37.5–150 mg). A Marketing Authorisation Application for these indications is under review with the European Medicines Agency. This phase 3 study assessed safety and efficacy of solriamfetol in participants with narcolepsy types 1 and 2 (NT1/2). 1 Methods: In this 12-week, double-blind, randomised, placebo-controlled study, participants with or without cataplexy were randomised to solriamfetol 75 mg, 150 mg, 300 mg, or placebo. Eligibility criteria: NT1/2 diagnosis; mean sleep latency <25 minutes on Maintenance of Wakefulness Test (MWT); Epworth Sleepiness Scale (ESS) score ≥10. Exclusion criteria: medications that could affect EDS or cataplexy; night-time or variable shift work; other conditions causing EDS. Results: 236 participants received ≥1 dose of solriamfetol (67.2% female; 80.2% white). Baseline MWT mean sleep latency: 7.5 minutes; baseline ESS score: 17.2. Solriamfetol significantly increased MWT sleep latency at week 12 (P<0.0001 for 300 mg and 150 mg); least squares (LS) mean change: 12.3 minutes for 300 mg, 9.8 for 150 mg, 4.7 for 75 mg, and 2.1 for placebo. Solriamfetol significantly decreased ESS scores at week 12 (P<0.0001 150 mg and 300 mg; P<0.05 75 mg). LS mean change in ESS: -6.4 for 300 mg, -5.4 for 150 mg, -3.8 for 75 mg, and -1.6 for placebo. Most common treatment-emergent adverse events (TEAEs; ≥5%): headache, nausea, decreased appetite, nasopharyngitis, dry mouth, and anxiety. Discontinuations due to TEAEs were more frequent in solriamfetol 150 mg and 300 mg groups. Discussion: Solriamfetol improved wakefulness and reduced EDS in participants with NT1/2. Most AEs were mild to moderate. Support: Jazz Pharmaceuticals. Reference: Thorpy MJ, et al. Ann Neurol 2019;85(3):359–370.